MEMS Smart Glass with Larger Angular Tuning Range and 2D Actuation - Md Kamrul Hasan; Mustaqim Siddi Que Iskhandar; Steffen Liebermann; Shilby Baby; Jiahao Chen; Muhammad Hasnain Qasim; Dennis Löber; Roland Donatiello; Guilin Xu; Hartmut Hillmer (Micromachines)
Millions of electrostatically actuatable micromirror arrays have been arranged in between windowpanes in inert gas environments, enabling active daylighting in buildings for illumination and climatization. MEMS smart windows can reduce energy consumption significantly. However, to allow personalized light steering for arbitrary user positions with high flexibility, two main limitations must be overcome: first, limited tuning angle spans by MEMS pull-in effects; and second, the lack of a second orthogonal tuning angle, which is highly required. Firstly, design improvements of electrostatically actuatable micromirror arrays are reported by utilizing tailored bottom electrode structures for enlarging the tilt angle (Φ). Considerably larger tuning ranges are presented, significantly improving daylight steering into buildings. Secondly, 2D actuation means free movement of micromirrors via two angles—tilt (Φ) and torsion angle (θ)—while applying two corresponding voltages between the metallic micromirrors and corresponding FTO (fluorine-doped tin oxide) counters bottom electrode pads. In addition, a solution for a notorious problem in MEMS actuation is presented. Micromirror design modifications are necessary to eliminate possible crack formation on metallic structure due to stress concentration during the free movement of 2D actuatable micromirror arrays. The concept, design of micromirror arrays and bottom electrodes, as well as technological fabrication and experimental results are presented and discussed.